2009
DOI: 10.1111/j.1365-2109.2008.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on survival and growth of the marine pejerreyOdontesthes argentinensislarvae

Abstract: Aquaculture Research, 2009, 40, 252^255 E¡ects of photoperiod on survival and growth L S Freitas et al. r 2008 Blackwell Munksgaard No claim to original US government works, Aquaculture Research, 40, 252^255

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Lower SGR rates were observed in larvae subjected to low a photoperiod (6L:18D) treatment. FREITAS et al (2009) reported higher SGR values for king fish (Odontesthes argentinensis) larvae in greater photoperiods. According to these authors, the Table 1 -Mean and standard deviation of temperature, dissolved oxygen, pH, and electrical conductivity for the piabanha-of-Pardo larvae, submitted under different hours of light during the trial period.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Lower SGR rates were observed in larvae subjected to low a photoperiod (6L:18D) treatment. FREITAS et al (2009) reported higher SGR values for king fish (Odontesthes argentinensis) larvae in greater photoperiods. According to these authors, the Table 1 -Mean and standard deviation of temperature, dissolved oxygen, pH, and electrical conductivity for the piabanha-of-Pardo larvae, submitted under different hours of light during the trial period.…”
Section: Resultsmentioning
confidence: 94%
“…Lower values of Fulton´s condition factor (minimum) were found to an intermediate photoperiod around 11 hours of light per day, obtained by derivative of the equation. FREITAS et al (2009) reported that greater Fulton´s condition factor values were observed for the 18L:6D and the 24L:0D photoperiods, than in the 12L:12D and the 0L:24D photoperiods. Photoperiods with 6 and 11 hours of light per day should be viewed with caution in the larval rearing of this species.…”
Section: Resultsmentioning
confidence: 95%
“…The obtained value (6.22 mm) was quite similar to the value reported by Brown and Fuentes (2005) for Odontesthes bonariensis larvae (6.7 mm). Freitas et al (2009) determined size after hatching around 7.2 mm for larvae of Odontesthes argentinensis (Valenciennes, 1835). The LairdeGompertz model has been successfully used to describe larval and juvenile growth of marine fishes (Dul ci c and Kraljevic, 1996;Plaza et al, 2008;Brown and S anchez, 2010) The LairdeGompertz model explained properly the growth in length for Odontesthes nigricans juveniles because an asymptotic trend was detected for larger specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of ammonia and alkalinity were performed daily according to the methodology described by UNESCO (1983), whereas nitrite was measured by the method of Strickland and Parsons (1972). The photoperiod was maintained at 18 light:6 dark, according to the method of Freitas et al (2009).…”
Section: Methodsmentioning
confidence: 99%